Reputation rules [ strategies for building your company's most valuable asset - Diermeier, Daniel (McGraw-Hill, 2011)
A Kellogg School of Management professor sets the benchmark for using reputation as a vital part of corporate strategy -- 9. Andersen before the fall : values, culture, and the teachable moment